Migrace z východoslovenské vesnice. Historický přehled a současné modely - Ort, Jan (Romano džaniben, 2016)
The article presents the results of a long-term ethnographic research in a village in north-eastern Slovakia. It focuses on the topic of work migration of local Roms into the Czech Republic, based on a detailed insight into the situation in its source locality. The migration is perceived in synchronic as well as diachronic perspective, and placed into the context of migration of the local population in general, as well as in the context of economic strategies pursued by its Romani inhabitants in particular. The work migration is also compared with another important strategy of socio-economic mobility, the movement of Roms from the local Romani settlement into the non-Romani village neighbourhood.